The Analysis of Student’s Mathematical Communication Ability on The Ethno-Mathematics Based Thinking Aloud Pairs Problem Solving (TAPPS) Learning - Werdiningsih, Endang; Masrukan, Masrukan; Junaedi, Iwan (Journal of Primary Education, 2019)
This research aims to (1) find out the quality the ethno-mathematics of Thinking Aloud Pairs Problem Solving (TAPPS) learning (2) discover the pattern of mathematic communication ability the ethno-mathematics of Thinking Aloud Pairs Problem Solving (TAPPS) learning.  This research uses mixed method type with concurrent embedded design. Quantitative and qualitative research runs together which the qualitative research is as the primer method. The qualitative learning is assessed from (1) planning and preparation, (2) classroom environment and instruction, and (3) evaluation (professional responsibility) stages. The result of this studies shows that the qualitative learning the ethno-mathematics of Thinking Aloud Pairs Problem Solving (TAPPS) is a good categorized. The pattern of student’s mathematic communication with upper group is a student who can explain their ideas and situation in written language appropriately.  Students who can express their ideas and situation on the facing problem in mathematics model appropriately and correctly. A student who can use the mathematical formula correctly to solve the problem. The pattern of student’s mathematic communication with medium group is a student who can explain the ideas and situation in written language appropriately. A student who can express their ideas and situation facing the problem into mathematic mode appropriately and correctly. The student who is not able to use the formula to face the problem. The pattern of student’s mathematic communication with lower group is student who can express their ideas and situation in written language appropriately. A student who can express their ideas and situation facing the problem intro mathematic model appropriately and correctly. A student who is not able to use the mathematical formula correctly to solve the problem.